Undergraduate Students’ English Self-Efficacy and Technology-Assisted Self-Regulated Learning - F Ari Anggraini Sebayang; Muh. Hasan Basri; Dewi Christa Kobis; Yulianty Sanggelorang (ETERNAL (English Teaching Journal), 2026)
Greater access to learning sources resulting from the advancement of the Internet and information technology helps students regulate their learning habits and achieve specific learning targets, including English language learning. This study analyzed English self-efficacy and technology-assisted self-regulated learning strategies among undergraduate students and how the two variables correlate. A total of 510 undergraduate students at Sam Ratulangi University, Indonesia, participated in the study. Two sets of questionnaires, including the Questionnaire of English Self-Efficacy (QESE) and the Technology-Based Self-Regulated Learning Strategy Questionnaire (TSRLQ), were administered in data collection. The data analyses included descriptive statistics and bivariate Pearson correlation calculations. This study found a heterogeneous profile of English self-efficacy and technology-assisted SRL. Meanwhile, the Pearson correlation calculation results revealed that English self-efficacy was significantly correlated with technology-assisted SRL in a positive direction. Thus, this study suggests that more efficacious students are more likely to apply technology-assisted SRL in their English language learning.